PEMANFAATAN PERPUSTAKAAN SEBAGAI SUMBER BELAJAR BAHASA INDONESIA SISWA SEKOLAH DASAR - Mujib; Ruli Astuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was conducted with the aim of finding out how the library at SDN Tempel, Krian District is used as a learning resource as well as the supporting and inhibiting factors in utilizing these facilities. The approach used in this research is a qualitative approach. This research is a type of descriptive research. The data collection technique is triangulation, namely data collection techniques can be carried out using observation, interviews and documentation as well as a combination of the three. The results of the research can be concluded that the library at SDN Tempel, Krian District is very good at supporting Indonesian language learning, in terms of facilities and infrastructure it meets library standards, there are only a few facilities that are incomplete.